Instrumental texture and sensory characteristics of freeze-dried starfruit snacks with added trehalose and sucrose = Textura instrumental y características sensoriales de snacks de carambola liofilizada con adición de trehalosa y sacarosa = Textura instrumental e características sensoriais de snacks de carambola liofilizada com adição de trealose e sacarose - Guberman, Mariela; Soteras, Trinidad; Méndez, Iván; Galmarini, Mara Virginia (Laboratorio Tecnológico del Uruguay (LATU), 2025)
This study assessed the impact of sucrose and trehalose as osmotic agents on the quality of freeze-dried starfruit snacks, with particular emphasis on sensory and textural attributes. Starfruit slices were subjected to three pre-treatments before freeze-drying: a control (no dehydration agent), osmotic dehydration in a sucrose solution (ODSAC), and osmotic dehydration in a trehalose solution (ODTRE). The resulting dehydrated samples were analyzed for water activity (aw), instrumental color and texture, and sensory attributes, including consumer acceptability. Both osmotic treatments significantly altered the instrumental texture of the starfruit slices compared to the control. Sensory analysis revealed significant differences in appearance, texture, flavor, and odor among treatments, with the ODTRE treatment receiving the highest acceptability scores. These findings suggest that using trehalose as an osmotic agent enhances the quality attributes of the dehydrated starfruit slices, supporting their potential as a fruit snack option.